Pediatric endoscopy in times of pandemic: A nationwide retrospective analysis - Łukasz Dembiński; Urszula Grzybowska-Chlebowczyk; Ewa Toporowska-Kowalska; Jarosław Walkowiak; Beata Gładysiewicz; Maciej Dądalski; Bartosz Korczowski; Elżbieta Czkwianianc; Maciej Zagierski; Elżbieta Jarocka-Cyrta; Anetta Soroczyńska-Wrzyszcz; Tomasz Pytrus; et al. (Journal of Infection and Public Health, 2024)
Background: Gastrointestinal endoscopy is a procedure that carries an increased risk of transmission of SARS-CoV-2 infection to medical staff. In patients, COVID-19 is a risk factor for adverse events of medical procedures. This study analyzed the real-life risk of, and factors contributing to, infection transmission to endoscopic personnel, and possible adverse events of the endoscopy procedure and anesthesia in children with COVID-19. Methods: Nationwide retrospective analysis of medical records of children with confirmed SARS-CoV-2 infection who underwent gastrointestinal endoscopy in Poland between February 2020 and February 2022. Results: Fifty-eight patients were included in the analysis, 35% of whom had COVID-19 symptoms at the time of endoscopy. The dominant indications for endoscopy were foreign body or corrosive substance ingestion and gastrointestinal bleeding. Nine cases of virus transmission were registered among endoscopic personnel. In all of these cases, the endoscopy team was unaware of the patient's infection (p < 0.01), although symptoms were present in 78% of the children. Lack of use of personal protective equipment was the strongest predictor of SARS-CoV-2 transmission (p < 0.01). The risk of infection was not statistically significantly dependent on the method of anesthesia, intubation or the type of endoscopy. No statistically significant correlation was found between symptomatic infection and adverse events of endoscopy or anesthesia occurrence. There was one reported anesthesia-related adverse event involving extubation difficulties due to worsening respiratory infection symptoms. Conclusions: The risk of transmitting SARS-CoV-2 to endoscopic personnel during procedures in children is low and depends on compliance with infection prevention and control measures. Performing gastrointestinal endoscopy in children with COVID-19 does not appear to be associated with an increased risk of adverse events.